Challenges in Digitisation - Paper given in honour of Esko Häkli, Helsinki, 23 November 2001 - Mittler, Elmar (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2004)
The digitisation of information seems to be the realization of mankind’s dream. We can - in principle - get seamless information everywhere and at any time. Digital information seems therefore to be a victory in terms of space and time. But, on the contrary, if we look at the reality of digital information on the World Wide Web, it sometimes looks more like a nightmare because of the overwhelming mass of material, lack of quality control, and lack of stability. For these reasons electronic information presents a real challenge to libraries, the ’professional information institutes’ of the world. Three main aspects of digitisation and the digital library will be discussed in this paper: · Retro-digitisation · Research and the digital library · Publishing as a distributed system